2002
DOI: 10.1161/01.atv.0000039169.47943.ee
|View full text |Cite
|
Sign up to set email alerts
|

B-Lymphocyte Deficiency Increases Atherosclerosis in LDL Receptor–Null Mice

Abstract: Objective-Atherosclerosis is an inflammatory disease characterized by innate and adaptive immune responses. We investigated the role of B cells and antibodies in the development of atherosclerosis in low density lipoprotein (LDL) receptor-deficient (LDLR Ϫ/Ϫ ) mice. Methods and Results-Using wild-type and B cell-deficient mice as bone marrow donors, we were able to generate LDLR Ϫ/Ϫ mice that possessed Ͻ1.0% of their normal B cell population. B cell-deficient LDLR Ϫ/Ϫ mice on a Western diet showed marked decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
195
3
7

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 303 publications
(216 citation statements)
references
References 52 publications
11
195
3
7
Order By: Relevance
“…As recently demonstrated, without the natural immunoprotection afforded by B cells, atherogenesis can be dramatically accelerated (55). In particular, B-1 cells are primitive tiers of innate immunity and arise spontaneously in mice early in ontogeny (56).…”
Section: Discussionmentioning
confidence: 99%
“…As recently demonstrated, without the natural immunoprotection afforded by B cells, atherogenesis can be dramatically accelerated (55). In particular, B-1 cells are primitive tiers of innate immunity and arise spontaneously in mice early in ontogeny (56).…”
Section: Discussionmentioning
confidence: 99%
“…141 Similarly, B cell deficiency increases atherosclerosis in Ldlr -/-mice. 142 One later study has suggested that B1a cells and their secretion of IgM mediate the protective effects of B cells. 143 Although these data indicate an atheroprotective function of B cells in atherosclerosis, B cell depletion with anti-CD20 was shown to protect against atherosclerosis in Apoe -/-and Ldlr -/-mice, 144 suggesting the contrary.…”
Section: Targeting Effector T Cell Responsesmentioning
confidence: 99%
“…Data from Major et al indicate that B-cell deficiency in LDL-receptor Ϫ/Ϫ mice increases atherosclerosis. 48 B-cells from LDL-receptor Ϫ/Ϫ and apoE Ϫ/Ϫ mice produce antibodies that recognize oxidized LDL and immunization of atherosclerotic mice with modified forms of LDL has been shown to reduce lesion development. 49,50 As noted, OPG Ϫ/Ϫ mice have immature B-cell development and impaired antibody production and administration of recombinant OPG stimulates production of specific antibodies.…”
Section: Bennett Et Al Opg Atherosclerosis and Calcificationmentioning
confidence: 99%